2008
DOI: 10.1073/pnas.0808360105
|View full text |Cite
|
Sign up to set email alerts
|

Aptamer-based endocytosis of a lysosomal enzyme

Abstract: Enzyme replacement therapy for lysosomal storage diseases is currently based on endocytosis of lysosomal enzymes via the mannose or mannose 6-phosphate receptors. We are developing a technology for endocytosis of lysosomal enzymes that depends on generic, chemically conjugated reagents. These reagents are aptamers (singlestranded nucleic acid molecules) selected to bind to the extracellular domain of the mouse transferrin receptor. After selection, an RNA aptamer and a DNA aptamer were modified with biotin and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
120
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(127 citation statements)
references
References 38 publications
1
120
0
1
Order By: Relevance
“…Transferrin receptors (TfRs) are particularly interesting aptamer targets for delivery strategies as TfRs are highly expressed on endothelial cells and are known to be involved in transcytosis across the BBB. Both RNA (FB4) and DNA (GS24) aptamers that bind to mouse TfRs have been selected [143]. Each of the FB4 and GS24 aptamers has shown cellular internalization.…”
Section: Aptamers For Transferrin Receptorsmentioning
confidence: 99%
“…Transferrin receptors (TfRs) are particularly interesting aptamer targets for delivery strategies as TfRs are highly expressed on endothelial cells and are known to be involved in transcytosis across the BBB. Both RNA (FB4) and DNA (GS24) aptamers that bind to mouse TfRs have been selected [143]. Each of the FB4 and GS24 aptamers has shown cellular internalization.…”
Section: Aptamers For Transferrin Receptorsmentioning
confidence: 99%
“…Aptamers can be covalently bound to a wide variety of therapeutic agents, including chemotherapeutics or enzymes (45,46), siRNA (47,48), or drug-loaded nanocarriers (36,49), to provide targeted drug delivery. The spatiotemporal control of drug delivery afforded by our approach may enhance the efficacy and therapeutic index of many drugs.…”
Section: Discussionmentioning
confidence: 99%
“…We found that the FITC fluorescence of aptamers 41, 43, and 32 appeared to be localized within the nuclei, whereas aptamers 41 and 43 were also present in the cytoplasm. The transportation of the aptamers into the cells may have occurred through endocytosis [25,26] ; therefore, we hypothesized that some of these aptamers may recognize EGFRvIII. Aptamer 47 also localized to the cell surface.…”
Section: Specificity Of the Aptamers For The U87δ Cellsmentioning
confidence: 99%